2011
DOI: 10.1073/pnas.1109796108
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle-like lipidome of human cytomegalovirus virions reveals a role for SNARE machinery in virion egress

Abstract: Human cytomegalovirus induces and requires fatty acid synthesis. This suggests an essential role for lipidome remodeling in viral replication. We used mass spectrometry to quantify glycerophospholipids in mock-infected and virus-infected fibroblasts, as well as in virions. Although the lipid composition of mock-infected and virus-infected fibroblasts was similar, virions were markedly different. The virion envelope contained twofold more phosphatidylethanolamines and threefold less phosphatidylserines than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 60 publications
4
90
0
Order By: Relevance
“…The effects of compound C were profound, with most of the metabolome changes due to HCMV reversed in the presence of compound C. One exception involved cytidine diphosphate (CDP)- ethanolamine and CDP-choline, which are used in the Kennedy pathway of phosphatidylcholine and phosphatidylethanolamine synthesis and remained elevated in the HCMV-infected, compound C-treated cells. Phosphatidylethanolamines are strongly enriched in HCMV virions (30). Another involved N-acetylated amino acids (e.g., acetylaspartate, acetylglutamate, and acetylalanine).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of compound C were profound, with most of the metabolome changes due to HCMV reversed in the presence of compound C. One exception involved cytidine diphosphate (CDP)- ethanolamine and CDP-choline, which are used in the Kennedy pathway of phosphatidylcholine and phosphatidylethanolamine synthesis and remained elevated in the HCMV-infected, compound C-treated cells. Phosphatidylethanolamines are strongly enriched in HCMV virions (30). Another involved N-acetylated amino acids (e.g., acetylaspartate, acetylglutamate, and acetylalanine).…”
Section: Resultsmentioning
confidence: 99%
“…The lower organic layer was isolated, synthetic odd-carbon phospholipids (four per phospholipid class) were added as standards, and the solvent was evaporated. The resulting lipid film was dissolved in 100 l of 58:40:2 isopropanol, hexane, 100 mM NH 4 COOH (aqueous) (mobile phase A) (16). Samples containing n-butyl alcohol were extracted similarly, and 5 l of 10 g/ml 32:0 phosphatidylmethanol was added as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…t-SNARE proteins interact with vesicle SNARE (v-SNARE) proteins and subsequently mediate membrane fusion (45). Several previous reports demonstrated that the SNARE complex is involved in viral infection (46)(47)(48). Meier et al reported that siRNA-mediated knockdown of the SNARE protein VAMP3 resulted in the inhibition of endocytic intracellular trafficking of a bunyavirus, Uukuniemi virus, indicating that SNARE protein-mediated membrane fusion is needed for the efficient entry of Uukuniemi virus into cells (49).…”
Section: Mir-27 Inhibits Adenovirus Infectionmentioning
confidence: 99%